3H-Pyrroles from ketoximes and acetylene: synthesis, stability and quantum-chemical insight. Issue 21 (27th May 2015) - Shabalin, Dmitrii A.; Dvorko, Marina Yu.; Schmidt, Elena Yu.; Ushakov, Igor' A.; Protsuk, Nadezhda I.; Kobychev, Vladimir B.; Soshnikov, Dmitrii Yu.; Trofimov, Alexander B.; Vitkovskaya, Nadezhda M.; Mikhaleva, Al'bina I.; Trofimov, Boris A.
Abstract: Rare nonaromatic 3 H -pyrroles have been synthesized from ketoximes having only one C–H bond adjacent to the oxime function and acetylene under pressure (10–13 atm) at 70 °C in two-phase superbase media of KOH/DMSO/ n -hexane type, the yields ranging 8–36%. The effect of substituents, superbase nature and reaction conditions on yields of the target 3 H -pyrroles has been analyzed. Hydroxypyrroline/3 H -pyrroles interconversion as well as relative stability of model 3 H -pyrroles have been assessed quantum chemically (MP2/6-31++G**//B3LYP/6-31G**). Graphical abstract: